A Reflection on a Data Curation Journey - Lötter, Lucia (J Empir Res Hum Res Ethics, 2015)
This commentary is a reflection on experience of data preservation and sharing (i.e., data curation) practices developed in a South African research organization. The lessons learned from this journey have echoes in the findings and recommendations emerging from the present study in Low and Middle-Income Countries (LMIC) and may usefully contribute to more general reflection on the management of change in data practice.